Project-Based Learning and Problem-Based Learning: Challenges and Opportunities for Collaborative Classroom Management - Sa’adah, Juliana Tsara Himmatus; Aimah, Siti; Fakhruddin, Fathiyah Mohd (Islamic Studies and Development Center in Collaboration With Students' Research Center Universitas Negeri Padang, 2025)
This research examines the application of Project Based Learning (PjBL) and Problem Based Learning (PBL) in facilitating Collaborative Classroom Management one of the universities in Indonesia. The purpose of this study is to identify the challenges and opportunities that arise in these approaches to facilitate the implementation of classroom management as well as how students engage in collaborative learning. The research design used is qualitative with a case study approach. Data collection techniques are through interviews with students and lecturers, as well as classroom observations. The research informants numbered 20 people including the principal, lecturers, students and teaching staff. And the data analysis technique uses an interactive model including data reduction, data presentation, and drawing conclusions or verification. The results showed that both PjBL and PBL have the potential to improve collaborative classroom management, but some challenges such as inadequate resources, time constraints and diverse student abilities need to be addressed. Nonetheless, these approaches also offer opportunities for students to develop critical thinking, problem solving and communication skills. This study concludes that a well-structured implementation of PjBL and PBL, coupled with continuous support from lecturers can significantly improve collaborative classroom management.